Large volume donor plasmapheresis in inherited thrombophilia implicated in arterial thrombosis - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Background. Life-threatening complications following apheresis are rare, and include venous thrombosis. Arterial thrombosis following apheresis has not been reported. Case report. A 48 year old donor had cerebral infarction following large volume plasma donation. The outcome was fatal. He was found to be heterozygous for both methylene tetrahydrofolate reductase (MTHFR) 677C-T mutation and Prothrombin 20210G-A allele. Conclusion. This case suggests that large volume plasma donation may trigger arterial thrombotic events in inherited thrombophilia. Therefore, the effects of plasmapheresis on coagulation system should be studied thoroughly. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: plasmapheresis; prothrombin 2021OG-A; MTHFR 677C-T; thrombosis; FACTOR-V-LEIDEN; METHYLENETETRAHYDROFOLATE REDUCTASE C677T; PROTHROMBIN GENE MUTATION; MYOCARDIAL-INFARCTION; VENOUS THROMBOSIS; RISK FACTOR; COMMON MUTATION; 3'-UNTRANSLATED REGION; VARIANT G20210A; HEART-DISEASE